2017
DOI: 10.5272/jimab.2017233.1688
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the Fitting Accuracy of Cast and SLM Co-Cr Dental Bridges Using Cad Software

Abstract: ABSTRACT:The aim of the present paper is to investigate the fitting accuracy of Co-Cr dental bridges, manufactured by three technologies, with the newly developed method using CAD software. The four-part dental bridges of Co-Cr alloys were produced by conventional casting of wax models, casting with 3D printed patterns and selective laser melting. The marginal and internal fit of dental bridges was studied out by two methods -silicone replica test and CAD software. As the silicone replica test characterizes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Akçin et al [ 48 ] also reported that casting showed the best marginal fit followed by SLM, and milling showed poor fitness in a five-unit bridge. However, Dicova et al [ 49 ] reported experimental results that SLM has better marginal fit than casting in a three-unit bridge. If the marginal fit of SLM is improved, it will have more clinical advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Akçin et al [ 48 ] also reported that casting showed the best marginal fit followed by SLM, and milling showed poor fitness in a five-unit bridge. However, Dicova et al [ 49 ] reported experimental results that SLM has better marginal fit than casting in a three-unit bridge. If the marginal fit of SLM is improved, it will have more clinical advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additive technologies using metal-based materials are commonly applied for the production of prototypes and fully functional elements in the automotive and aviation industries [ 29 , 30 , 31 ] as well as in robotics [ 32 ]. Current metal powder-based technologies are widely used in the odontology industry, where it is not necessary to construct large, rather but strong and corrosion-resistant dentures [ 33 , 34 , 35 ]. The medical industry pays even more attention to the application of additive technologies.…”
Section: Introductionmentioning
confidence: 99%